2007
DOI: 10.1017/s0950268807009843
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of epidemic keratoconjunctivitis in a regional ophthalmology clinic in New South Wales

Abstract: The objective of the study was to identify the extent and cause of an outbreak of epidemic keratoconjunctivitis (EKC). The study design was active case finding and a case-control study of clinic patients who developed symptoms of EKC between 31 December 2005 and 31 March 2006. The main outcome measures were clinical procedures carried out and clinicians seen during clinic visit. Significantly more cases than controls had tonometry with instillation of anaesthetic drops (OR 16.5, 95% CI 3.9-145.1, P<0.01), opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 15 publications
(25 reference statements)
1
28
0
Order By: Relevance
“…2 For example, stethoscopes are known to harbor pathogenic bacteria, including Staphylococcus aureus, coliforms, Pseudomonas, and Clostridium difficile?' 5 Viable multidrug-resistant organisms (eg, vancomycin-resistant Enterococci [VRE]) have been found on portable medical equipment (eg, blood pressure cuffs and computer keyboards) used in the room of a patient infected or colonized with the same multidrug-resistant organism. 6 VRE was isolated from physicians' stethoscopes in 31% of cases after being in contact with patients colonized with VRE.…”
Section: Monitoring Of Cleaning Practices For Portable Multiuse Medimentioning
confidence: 99%
See 1 more Smart Citation
“…2 For example, stethoscopes are known to harbor pathogenic bacteria, including Staphylococcus aureus, coliforms, Pseudomonas, and Clostridium difficile?' 5 Viable multidrug-resistant organisms (eg, vancomycin-resistant Enterococci [VRE]) have been found on portable medical equipment (eg, blood pressure cuffs and computer keyboards) used in the room of a patient infected or colonized with the same multidrug-resistant organism. 6 VRE was isolated from physicians' stethoscopes in 31% of cases after being in contact with patients colonized with VRE.…”
Section: Monitoring Of Cleaning Practices For Portable Multiuse Medimentioning
confidence: 99%
“…4 ' 5 In several studies, many organisms have been grown from ophthalmology solutions that were used on multiple patients in a variety of settings, including a primary care setting, ophthalmology clinics, and long-term care facilities. These include normal skin contaminants, such as coagulasenegative Staphylococcus, Propionbacterium acnes, and Streptococcus viridans, as well as pathogens such as Pseudomonas putida, Burkholderia cepacia, and Serratia marcescans.…”
mentioning
confidence: 99%
“…Outbreaks of epidemic ocular infections have occurred in ophthalmology clinics in medical centres around the world in the past several years, [1][2][3] with insufficient disinfection of Goldmann tonometer prisms being implicated as a potential source of transmission. 4 Epidemiological and clinical studies of epidemic keratoconjunctivitis outbreaks in ophthalmology clinics have demonstrated that tonometer tips, contaminated eye drops, and contact with infected healthcare workers are vehicles for transmission of adenovirus serotypes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Epidemiological and clinical studies of epidemic keratoconjunctivitis outbreaks in ophthalmology clinics have demonstrated that tonometer tips, contaminated eye drops, and contact with infected healthcare workers are vehicles for transmission of adenovirus serotypes. 3,5,6 Adenovirus can survive for 7-14 days at room temperature on a dry surface and is resistant to 70% isopropyl alcohol, 7 which is often used in busy clinic settings. 8 Improper sterilization techniques also increase the risk of corneal injury and burn secondary to residual cleansing solution on reusable Goldmann prisms.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Ophthalmology offices are prone to epidemics due to contamination of instruments or hand-eye contact by ocular secretions from the infected patient. 10 In addition, EKC has been found in hospital outbreaks, public swimming pools, and upper respiratory tract infections. 11 Epidemic keratoconjunctivitis is characterized by follicular conjunctivitis, papillary hypertrophy, conjunctival hemorrhage, lid edema, and chemosis.…”
mentioning
confidence: 99%